Wave forces on offshore structures - Sarpkaya, Turgut, 1928- (Cambridge University Press, 2010)
A thorough understanding of the interaction of waves and currents with offshore structures has now become a vital factor in the safe and economical design of various offshore technologies. There has been a significant increase in the research efforts to meet this need. Although considerable progress has been made in the offshore industry and in the understanding of the interaction of waves, currents, and wind with ocean structures, most of the available books concentrate only on practical applications without a grounding in the physics. This text integrates an understanding of the physics of ocean-structure interactions with numerous applications. This more complete understanding will allow the engineer and designer to solve problems heretofore not encountered, and to design new and innovative structures. The intent of this book is to serve the needs of future generations of engineers designing more sophisticated structures at ever increasing depths.